Kesehatan Psikososial dan Mekanisme Koping Mahasiswa Kesehatan di Masa Pandemi Covid-19 - Nurlaila Fitriani; Annisa Fais Pradevi; Nava Nofita Kustiaverawati (FORIKES, 2022)
Online exams and practicums and too many assignments cause anxiety for students, especially during the Covid-19 pandemic. This will affect the psychosocial condition of students which can have an impact on decreasing interest in learning, decreasing achievement and even psychosocial disorders in students. The purpose of this study was to determine the relationship between psychosocial health and coping mechanisms in health students during the Covid-19 pandemic. This type of research was quantitative with a correlative design. The sampling technique used was purposive sampling. Data were collected through filling out a questionnaire, namely DASS (Depression Anxiety Stress Scale) and coping methods. The results showed that most of the health students carried out adaptive coping mechanisms for the psychosocial health they experienced during the COVID-19 pandemic. Furthermore, it was concluded that there was a relationship between psychosocial health and coping mechanisms in health students during the Covid-19 pandemic.Keywords: Covid-19 pandemic; college student; psychosocial; coping mechanism ABSTRAK Ujian dan praktikum secara online dan tugas yang terlalu banyak menimbulkan kecemasan bagi mahasiswa, apalagi di masa pandemi Covid-19. Hal ini akan mempengaruhi kondisi psikososial mahasiswa yang bisa berdampak pada menurunnya minat belajar, menurunnya prestasi bahkan gangguan psikososial pada mahasiswa. Tujuan penelitian ini adalah untuk mengetahui hubungan antara kesehatan psikososial dengan mekanisme koping pada mahasiswa kesehatan di masa pandemi Covid-19. Jenis penelitian ini adalah kuantitatif dengan desain korelatif. Teknik pengambilan sampel yang digunakan adalah purposive sampling. Data dikumpulkan melalui pengisian kuesioner yaitu DASS (Depression Anxiety Stress Scale) dan cara koping. Hasil penelitian menunjukkan bahwa pada sebagian besar mahasiswa kesehatan melakukan mekanisme koping adaptif terhadap kesehatan psikososial yang dialaminya selama pandemi COVID-19. Selanjutnya disimpulkan bahwa ada hubungan antara kesehatan psikososial dengan mekanisme koping pada mahasiswa kesehatan selama masa pandemi Covid-19.Kata kunci: pandemi Covid-19; mahasiswa; psikososial; mekanisme koping